Physiological and biochemical aspects of lettuce seed germination at different temperatures - Catão, Hugo Cesar Rodrigues Moreira; Gomes, Luiz Antônio Augusto; Santos, Heloisa Oliveira dos; Guimarães, Renato Mendes; Fonseca, Pedro Henrique Faria; Caixeta, Franciele (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the electrophoretic patterns of heat‑tolerant proteins and the activity of the endo‑β‑mannanase enzyme during lettuce seed germination, at high temperature. Seeds of eight lettuce cultivars were subjected to germination, first count, and emergence tests at two temperatures, 20 and 35°C. The index of germination speed (IVG) and the emergence rate index (IVE) were calculated. The expression of heat‑tolerant proteins and of the endo‑β‑mannanase enzyme was also evaluated for all treatments. The experimental design was completely randomized, in a 2x8 factorial arrangement, with two temperatures and eight cultivars. The highest germination is observed at 35°C in the Everglades cultivar, considered thermotolerant. The patterns of heat‑tolerant proteins in lettuce seeds present specific bands in the Everglades cultivar, at 35ºC. The activity of the endo‑β‑mannanase enzyme is higher in the Everglades cultivar, at this temperature. This cultivar has potential for use in lettuce breeding programs aiming for tolerance to high temperatures during germination.